PENERAPAN KESELAMATAN KERJA DI MC CLEAN LAUNDRY GRAND JATRA HOTEL PEKANBARU - Atiqah Hayuning Sari; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The increasing number of tourists defend on the hotel presence. In Pekanbaru, increased the number of guests visiting to Grand Jatra Hotel Pekanbaru, it also affects to increased of laundry service. Laundry section need to apply work safety standard for employee. Work safety is all possibilities reduce accidents while staff works. This research aims to understand safety work in Mc Clean Laundry. This research is conducted by applying descriptive qualitative method based on data collection techniques as observation, deep interview, and documentation. Safety work cover report dangerous condition, obey the ban, operate on tools, handle risky items, saving all materials, and wear safety clothes. Based on the result of research that has been done, it can be included that operate safety work in Mc Clean Laundry is not according to standard. Keywords: Hotel, Laundry, Safety Work